Reactualization of Islamic Religious Education in Facing the Challenges of the Digital Era - Muh Ibnu Sholeh Sholeh; Lutfi Firdausi; siti Fatinnah binti Ab Rahman (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
advancement and the preservation of humanistic and ethical values in education. The research aims to analyze strategic efforts to integrate digital transformation into PAI learning while maintaining its moral, spiritual, and character-building orientation. This study employs a qualitative approach using library research methods by reviewing scholarly books, journal articles, and relevant academic documents. Data were analyzed through content analysis involving data reduction, thematic categorization, interpretation, and conceptual synthesis. The findings indicate that the reactualization of PAI requires pedagogical integration of digital technology, adaptive curriculum development, strengthening of educators’ digital competencies, cultivation of digital ethics among learners, and holistic evaluation emphasizing cognitive, affective, and spiritual dimensions. These strategies demonstrate that technology should function as an educational instrument supporting value formation rather than replacing human interaction in learning. The study implies that philosophical and ethical guidance is essential to ensure that digital-based PAI learning contributes to holistic human development and remains aligned with the fundamental goals of Islamic education.